Interaction of inter- and intralaminar damage in scaled quasi-static indentation tests: Part 1 – Experiments. (February 2016) - Abisset, E.; Daghia, F.; Sun, X.C.; Wisnom, M.R.; Hallett, S.R.
Abstract: The evaluation of the predictive capabilities of models proposed in the literature for laminated composites calls for experimental testing providing detailed results of both the global and local response in terms of degradation mechanisms, such as delamination, transverse cracking and fibre breaking. Scaled tests, in which one or more characteristic dimensions are modified, allow variation of the different mechanisms. In this paper, a unique series of scaled indentation tests are performed on quasi-isotropic composite plates, and a detailed assessment of the damage evolution is carried out through non-destructive techniques, including ultrasonic C-scan and X-ray Computed Tomography (CT). Four different configurations are tested, presenting changes in both in-plane dimensions and fully three dimensional scaled cases. The latter are performed with sublaminate and ply scaling to show the effect of ply thickness on response. A detailed set of results for both global behaviour and the damage evolution is provided to demonstrate the mechanisms controlling behaviour and to create a reference set of data for model validation. The scaling effects observed are also discussed making use of simplified analytical models.